Forbidding the tragedy of commons; conserving indigenous knowledge through indigenous peoples and local communities entitlement for future generations from the perspectives of intergeneration justice - Mohd Khalid, Al-Hanisham; Nordin, Rohaida; Mohd Hussein, Safinaz (Science Publishing Corporation Inc, 2018)
Conserving indigenous knowledge (IK) has long been discussed in international fore for more than five decade.The core issues is there is unanimity among scholars, governments, indigenous peoples and local communities on whether and how issue of IK could be harmonise within intellectual property rights law framework particularly copyrights. This paper aims to highlight the issues of conserving indigenous knowledge since indigenous knowledge does not belong to one generation but all generations. Discussion will embark on from the perspective of intellectual property jurisprudence through the works of Henry Reynolds, James Tully and Will Kymlicka.The outcome of this paper demonstrates promising thought into the role of intergeneration justice in protecting indigenous peoples in Malaysia.It is the contention of this paper that perhaps such conditions could apply to traditional knowledge too in addressing the plight of indigenous peoples.